2017
DOI: 10.1016/j.joca.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Acute mobilization and migration of bone marrow-derived stem cells following anterior cruciate ligament rupture

Abstract: ACL rupture induced peripheral blood mobilization of MSCs and migration of intravenously-injected allogenic MSCs to the injured joint, where they localized in the synovium and quadriceps MTJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…Mannose is a monosaccharide involved in protein N‐glycosylation, which is integral to several physiologic functions including lectin‐mediated cell‐cell interactions. One hypothesis is that reduced serum mannose reflects consumption in N‐glycosylation associated with stem and immune cell trafficking to the injured joint, which we have observed in this model . Urita et al described decreased concentrations of N‐glycan species in both human and murine osteoarthritic articular cartilage and demonstrated a correlation between high mannose N‐glycans and chondrocyte production of matrix‐degrading enzymes MMP‐13 and ADAMTS‐5 in response to interleukin‐1α stimulation .…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Mannose is a monosaccharide involved in protein N‐glycosylation, which is integral to several physiologic functions including lectin‐mediated cell‐cell interactions. One hypothesis is that reduced serum mannose reflects consumption in N‐glycosylation associated with stem and immune cell trafficking to the injured joint, which we have observed in this model . Urita et al described decreased concentrations of N‐glycan species in both human and murine osteoarthritic articular cartilage and demonstrated a correlation between high mannose N‐glycans and chondrocyte production of matrix‐degrading enzymes MMP‐13 and ADAMTS‐5 in response to interleukin‐1α stimulation .…”
Section: Discussionsupporting
confidence: 58%
“…Further, Chen et al demonstrated that increasing kynurenine levels via indoleamine 2,3‐dioxygenase (IDO)‐targeted gene therapy promoted the resolution of collagen‐induced arthritis, primarily by apoptosis of T‐cells and reduction in synovial IL‐17. We previously demonstrated that our ACL injury model leads to acutely increased IL‐17 expression in synovium . Given the presently demonstrated reduction in tryptophan metabolites that could serve as AHR ligands in ACLR animals, we hypothesize that a pro‐inflammatory environment is favored in the acute period after injury.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…T. Maerz et al reported that the myotendinous junction (MTJ) of the quadriceps was also an important target in the acute mobilization of stem cells aer anterior cruciate ligament transection (ACLT). 39 Unfortunately, no signicant positive staining was found in the muscle or tendon, which was probably due to the difference in surgery and time. Surprisingly, abundant positive staining was found in part of the bone marrow cavity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ACLT is one of the most common sporting injuries and is associated with an increased risk for developing post‐traumatic osteoarthritis (PTOA) . The ACLT injury model has been shown to reliably reproduce the changes found in human osteoarthritic bone.…”
Section: Discussionmentioning
confidence: 99%